2021
DOI: 10.2319/012121-62.1
|View full text |Cite
|
Sign up to set email alerts
|

Root resorption associated with maxillary buccal segment intrusion using variable force magnitudes:

Abstract: Objectives To compare the root resorption resulting from miniscrew-supported maxillary posterior dentoalveolar intrusion using two different force magnitudes. Materials and Methods: Adult patients with skeletal open bite, indicated for maxillary posterior dentoalveolar intrusion, were recruited and randomly assigned to the comparison or intervention groups. The comparison group involved applying 200 g of intrusive force per s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 29 publications
1
29
0
1
Order By: Relevance
“…Skeletal open bite malocclusion is considered the most challenging malocclusion with respect to its treatment as well as stability [ 5 ]. One of the most common protocols to correct this malocclusion is by intruding posterior maxillary teeth [ 6 ]. Two main limiting factors for such treatment that might result in apical root resorption of the intruded teeth exist: (1) concentrated orthodontic force over a small apical surface area and, (2) proximity of the teeth to the maxillary sinus with its cortical bone lining.…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal open bite malocclusion is considered the most challenging malocclusion with respect to its treatment as well as stability [ 5 ]. One of the most common protocols to correct this malocclusion is by intruding posterior maxillary teeth [ 6 ]. Two main limiting factors for such treatment that might result in apical root resorption of the intruded teeth exist: (1) concentrated orthodontic force over a small apical surface area and, (2) proximity of the teeth to the maxillary sinus with its cortical bone lining.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the outcomes of the study indicated that the alveolar bone density of left first permanent molars had statistically significant decrease (461.02±162.29 HU) and non-significant decrease (59.43±179.72 HU) in the buccal and palatal side, respectively. Table (2,4,6) result, CBCT was utilized to assess bone density in this investigation. In the current study there was no statistical difference in bone density between male and female patients that were allocated.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the bone density, in the current study, was assessed at T1 and T2, T2 was determined to be on average period of 4.5 months for the range (3-6) months. This range is the time needed to achieve total molar intrusion with TADs as a treatment modality for AOB management [2,10,16].…”
Section: Resultsmentioning
confidence: 99%
“…Histological and metabolic pulp changes have been observed in patients under orthodontic treatment [2,34]. Moreover, apical root resorption (ARR) has been associated with intrusion forces [35,36]. Risk factors, such us the force magnitude, the age of the patient, the tooth type, the treatment duration and the range of movement, should be taken into consideration [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, apical root resorption (ARR) has been associated with intrusion forces [35,36]. Risk factors, such us the force magnitude, the age of the patient, the tooth type, the treatment duration and the range of movement, should be taken into consideration [36][37][38]. Variances observed between activations on the same axis (i.e., between intrusion and extrusion or oral and vestibular activation) have multifactorial etiology.…”
Section: Discussionmentioning
confidence: 99%